Problems related to acute respiratory infection among under-5 children in Sorong, West Papua: a community diagnosis approach - Edo Prabudi Thamrin; Risma Kristi Utami; Fabianto Santoso; Ayu Ashari Thamrin; Siti Syahral Ain; Trevino Aristarkus Pakasi (Journal of Community Empowerment for Health, 2019)
Acute respiratory infections (ARIs) are the leading cause of morbidity and mortality in children under five years, with a periodic prevalence of 25.9% in West Papua (2013). This study aims to explain the factors associated with ARIs in under-5 children in Sorong District, West Papua. This cross-sectional study was conducted in two districts, where trained medical students interviewed 135 mothers/caregivers by using a structured questionnaire and interviewed cadres and health workers for qualitative observation. About 85.5% of respondents stated that their children had ARIs in the previous two weeks (n=135), much higher than the data from Sorong District Health Office, which only reached 24.63%. Dominant risk factors were large household size, smoking at home, and improper handwashing habits. Only half of the respondents went to a physician in a primary care facility. Nearly half of the respondents had difficulty in accessing the facility. The majority of caregivers used over-the-counter or traditional medicine. Around 70% of respondents in Makbon Subdistrict did nothing to prevent the transmission of ARIs among children. ARIs remains a massive problem in the Sorong district. We need to educate the mothers/caregivers about the rational use of medicine and the prevention of ARIs, and also advocate for better access to clean water, sanitation, and healthcare facilities.